Novel reconstruction procedure after total gastrectomy: clinical application of adjustable double-channel digestive tract reconstruction of jejunal interposition - Zhou, Guomin; Yang, Yu; Chen, Jin; Tao, Xiaoliang; Zhou, Hangyu; Ming, Rui; Jiang, Huaiwu (Frontiers in Surgery, 2025)
BackgroundAlthough diverse reconstruction techniques exist after total gastrectomy for gastric cancer, they have limited effectiveness. Adjustable double-channel digestive tract reconstruction of jejunal interposition (a-DJI) is an improved approach. This study compares this procedure with Roux-en-Y (RY) anastomosis to assess its clinical efficacy post-gastrectomy.MethodsThe patients in this randomized controlled trial assigned patients to either the a-DJI group (experimental) or the RY group (control). Patients were followed for a total period of 1 year. Primary endpoints included perioperative indices; time to first flatus or feeding; complications (reflux esophagitis, dumping syndrome, and Roux retention syndrome); nutritional status (hemoglobin, total protein, albumin, vitamin D, and calcium); and dietary status.ResultsFrom January 2021 to February 2023, 77 patients were enrolled with 39 and 38 patients in the a-DJI and RY groups, respectively. Reconstruction time, intraoperative blood loss, or time to first flatus/feeding did not differ significantly between groups (all P > 0.05). The a-DJI group had significantly lower rates of reflux esophagitis, dumping syndrome, and Roux retention syndrome (all P < 0.05) than those in the RY group. The RY group was more likely to consume <300 ml per meal and >5 meals per day than the a-DJI group (all P < 0.05). Body weight, hemoglobin, total protein, and albumin levels decreased lesser in the a-DJI group than those in the RY group (all P < 0.05). Vitamin D and calcium levels were higher in the a-DJI group than those in the RY group (all P < 0.05).ConclusionThe a-DJI is superior to RY in reducing complications and improving nutritional status in patients with gastric cancer after total gastrectomy.